Ornamental Plants and Urban Gardening - László Orlóci; Albert Fekete (Plants, 2023)
Urban green areas serve both the mental and physical health of the people living in the settlements; therefore, the ornamental plants used on green areas currently have a prominent role in reducing the effects of climate change and urbanization, as well as in providing ecosystem services. This is a dynamically changing, new field that requires close cooperation with several scientific fields, such as landscape architecture and plant physiology, genetics, plant breeding, and ecology. The monitoring and research of settlement communities as ecological systems greatly serves the perception of the effects of climate change and helps to mitigate them. The sustainability and economic operation of established urban green space systems can be made effective by applying innovative technologies. The Special Issue “Ornamental Plants and Urban Gardening” was launched in 2022 and published 13 articles on the topic until 31 July 2023. The published articles also have a very wide spectrum of topics, which also shows the diversity and the interdisciplinary nature of the scientific field. In the following, we present the main topics of the published articles and the results with which their authors contributed to the enrichment of the scientific field. We present a brief summary of the articles in shorter subsections.